Validation of force fields of rubber through glass-transition temperature calculation by microsecond atomic-scale molecular dynamics simulation - Sharma, Pragati; Roy, Sudip; Karimi-Varzaneh, Hossein Ali (Journal of Physical Chemistry B, 2016)
Microsecond atomic-scale molecular dynamics simulation has been employed to calculate the glass-transition temperature (T-g) of cis- and trans-1,4-polybutadiene (PB) and 1,4-polyisoprene (PI). Both all-atomistic and united-atom models have been simulated using force fields, already available in literature. The accuracy of these decade old force fields has been tested by comparing calculated glass-transition temperatures to the corresponding experimental values. T-g depicts the phase transition in elastomers and substantially affects various physical properties of polymers, and hence the reproducibility of T-g becomes very crucial from a thermodynamic point of view. Such validation using T-g also evaluates the ability of these force fields to be used for advanced materials like rubber nanocomposites, where T-g is greatly affected by the presence of fillers. We have calculated T-g for a total of eight systems, featuring all-atom and united-atom models of cis- and trans-PI and-PB, which are the major constituents of natural and synthetic rubber. Tuning and refinement of the force fields has also been done using quantum-chemical calculations to obtain desirable density and T-g. Thus, a set of properly validated force fields, capable of reproducing various macroscopic properties of rubber, has been provided. A novel polymer equilibration protocol, involving potential energy convergence as the equilibration criterion, has been proposed. We demonstrate that not only macroscopic polymer properties like density, thermal expansion coefficient, and T-g but also local structural characteristics like end-to-end distance (R) and radius of gyration (R-g) and mechanical properties like bulk modulus have also been equilibrated using our strategy. Complete decay of end-to-end vector autocorrelation function with time also supports proper equilibration using our strategy.

Partially bio-based poly(amide imide)s by polycondensation of aromatic diacylhydrazides based on lignin-derived phenolic acids and aromatic dianhydrides: synthesis, characterization, and computational studies - Kuhire, Sachin S.; Sharma, Pragati; Chakrabarty, Suman; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
Two new bio-based diacylhydrazide monomers, namely, 4,4-(propane-1,3-diylbis(oxy))bis(3-methoxybenzohydrazide) and 4,4-(propane-1,3-diylbis(oxy))bis(3,5-dimethoxybenzohydrazide) were synthesized starting from lignin-derived phenolic acids, namely, vanillic acid and syringic acid. A series of poly(amide imide)s was synthesized by polycondensation of these diacylhydrazide monomers with commercially available aromatic dianhydrides. Poly(amide imide)s showed inherent viscosity in the range 0.44-0.56 dLg(-1) and exhibited good solubility in organic solvents. Poly(amide imide)s could be cast into transparent, flexible, and tough films from their N,N-dimethylacetamide solutions. Poly(amide imide)s showed 10% weight loss in the temperature range 340-364 degrees C indicating their good thermal stability. Glass transition temperature (T-g) of poly(amide imides)s were measured by DSC and DMA which were in the range 201-223 degrees C and 214-248 degrees C, respectively. The T-g values of poly(amide imide)s were dependent on the number methoxy substituents on aromatic rings of diacylhydrazide monomers. Molecular dynamics simulation studies revealed that chain rigidity is the dominant factor for observed trends in T-g. (c) 2017 Wiley Periodicals, Inc.
Keywords: Biobased Polymers; Computational studies; Glass-transaction temperature; lignin; Monomers; Plant oils; Polyimide; Reneable resources; Renewable resources; Step-growth polymers; structure-property relations; Sustanaible Polymers; Thermal night; Thermosetting resins; Vanillin

Molecular view of CO2 capture by polyethylenimine: role of structural and dynamical heterogeneity - Sharma, Pragati; Chakrabarty, Suman; Roy, Sudip; Kumar, Rajnish (Langmuir, 2018)
The molecular thermodynamics and kinetics of CO2 sorption in Polyethylenimine (PEI) melt have been investigated systematically using GCMC and MD simulations. We elucidate presence of significant structural and dynamic heterogeneity associated with the overall absorption process. CO2 adsorption in a PEI membrane shows a distinct two-stage process of a rapid CO2 adsorption at the interfaces (hundreds of picoseconds) followed by a significantly slower diffusion limited release toward the interior bulk regions of PEI melt (hundreds of nanoseconds to microseconds). The spatial heterogeneity of local structural features of the PEI chains lead to significantly heterogeneous absorption characterized by clustering and trapping of CO2 molecules that then lead to subdiffusive motion of CO2. In the complex interplay of interaction and entropy, the latter emerges out to be the major determining factor with significantly higher solubility of CO2 near the interfaces despite having lower density of binding amine groups. Regions having higher free-volume (entropically favorable) viz. interfaces, pores and loops demonstrate higher CO2 capture ability. Various local structural features of PEI conformations, for example, inter- and intrachain loops, pores of different radii, and di- or tricoordinated pores are explored for their effects on the varying CO2 adsorption abilities.

Soluble polybenzimidazoles with intrinsic porosity: synthesis, structure, properties and processability - Kumar, Vikas; Chatterjee, Shyambo; Sharma, Pragati; Chakrabarty, Suman; Avadhani, Chilukuri V.; Sivaram, Swaminathan (56Journal of Polymer Science Part A-Polymer Chemistry, 2018)
We have explored two novel comonomers, namely, 4,16-dicarboxyl[2.2]paracyclophane and 5,5,6,6-tetraamino-3,3,3,3-tetramethyl-1,1-spirobi[indane], for the synthesis of co-polybenzimidazoles (co-PBIs) with intrinsic porosity. Both these monomers possess twisted structures that can lead to awkward macromolecular shapes that cannot pack efficiently. The consequences of introducing these two monomers on the structure and properties of PBIs are reported. The random copolymers synthesized are amorphous and possess glass transition temperatures (T(g)s) greater than 400 degrees C. T-g decreases with increasing comonomer content indicating an increase in fractional free volume. The copolymers have low surface area. TEM and BET measurements show evidence of mesopore formation. The copolymers show significant carbon dioxide adsorption. Single chain molecular dynamics simulation of 24-mer repeat units shows intramolecular void spaces arising as a result of distorted polymer chain with reduced conformational mobility. These studies define a new synthetic strategy for bottoms-up synthesis of PBIs with intrinsic porosity. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1046-1057

Impact of plasticizer addition on molecular properties of polybutadiene rubber and its manifestations to glass transition temperature - Sharma, Pragati; Roy, Sudip; Karimi-Varzaneh, Hossein Ali (Macromolecular Theory and Simulations, 2019)
Effect of blending low and high T-g polymer on the structural, spatial, and temporal properties of the polybutadiene rubber are investigated using molecular dynamics simulations. It is elucidated that smaller chain length counterpart of polybutadiene (5mer-OB) acts as plasticizer for the polybutadiene rubber matrix (32mer-PB). Observed flexibility at macroscopic level by plasticizer addition is corroborated at the molecular level in the form of lower conformational rigidity and faster diffusion of polybutadiene chains in the mixtures. It is inferred that plasticizers decreases T-g of the matrix, due to cooperative influence of decreased chain packing and rigidity. Opposite effect is observed in mixtures with high T-g polymer, polystyrene. T-g of the mixtures showed substantial dependence on the type, concentration, chain length as well as miscibility of plasticizers in the matrix. However, the effect of increasing chain length is more pronounced but counter-controlled by the spatially heterogeneous distribution of the plasticizer. Clustering of polystyrene chains induced significant dynamic heterogeneity in the homogeneous polybutadiene matrix, which apparently lead to reduced plasticization effect. Addition of plasticizers in rubber induce discernible changes in the structural and dynamic properties of the rubber matrix, which manifest as the variation in glass transition and explains the real-life activity of plasticizers.
Keywords: Glass transition temperature; MD Simulation; plasticizer action; polybutadiene rubber; Polystyrene; spatial and dynamic heterogeneity

Glass transition temperature of polybutadiene and polyisoprene from high temperature segmental relaxation correlation using molecular dynamics - Sharma, Pragati; Roy, Sudip (Soft Materials, 2020)
Predicting glass transition temperature for rubber and rubber composites is immensely important for tire industry for the development of products and fine-tune process conditions. Molecular dynamics simulation is been used to predict glass transition temperature as a function of molecular-level structural changes, e.g., composition (functional groups), topology, and polymerization. However, prediction of glass transition temperature within experimental error bar from molecular dynamics simulation is only possible from all atomistic description (model) of the system as united atom and coarse-grained models under-predict the values. Conventional way of calculation of glass transition temperature from density (or any other properties which show sharp transition)-temperature plots are computationally very demanding because of atomistic simulations and simulations below the glass transition point, i.e., in glassy state. Here we report a novel method for calculation of glass transition temperature using only segmental relaxation correlation functions calculated at higher temperatures, i.e., above glass transition temperature. We have presented a protocol here and shown for two polymeric systems polybutadiene and polyisoprene. We believe this method cuts the computational cost of predicting glass transition temperature by one-third and will be applicable for industrial applications for structure-property validations.
Keywords: Glass transition temperature; molecular dynamics simulation; Polymers; rubber